2015
DOI: 10.1007/s00029-015-0178-x
|View full text |Cite
|
Sign up to set email alerts
|

On the derived category of the Hilbert scheme of points on an Enriques surface

Abstract: Abstract. We use semi-orthogonal decompositions to construct autoequivalences of Hilbert schemes of points on Enriques surfaces and of Calabi-Yau varieties which cover them. While doing this, we show that the derived category of a surface whose irregularity and geometric genus vanish embeds into the derived category of its Hilbert scheme of points.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 35 publications
0
28
0
Order By: Relevance
“…More recently, autoequivalences of the (bounded) derived categories D b (X [n] ) of the Hilbert schemes were intensively studied; see [Plo07], [Add11], [PS12], [Mea12], [Kru13], [CLS14], [KS14]. In particular, Addington [Add11] defined the notion of a P n -functor as a Fourier-Mukai transform F : D b (M ) → D b (N ) between derived categories of varieties with rightadjoint F R : D b (N ) → D b (M ) and the main property that In [Kru13] it was shown that for every smooth surface X and n ≥ 2 there is a P n−1 -functor H 0,n := H : D b (X) → D b…”
Section: Introductionmentioning
confidence: 99%
“…More recently, autoequivalences of the (bounded) derived categories D b (X [n] ) of the Hilbert schemes were intensively studied; see [Plo07], [Add11], [PS12], [Mea12], [Kru13], [CLS14], [KS14]. In particular, Addington [Add11] defined the notion of a P n -functor as a Fourier-Mukai transform F : D b (M ) → D b (N ) between derived categories of varieties with rightadjoint F R : D b (N ) → D b (M ) and the main property that In [Kru13] it was shown that for every smooth surface X and n ≥ 2 there is a P n−1 -functor H 0,n := H : D b (X) → D b…”
Section: Introductionmentioning
confidence: 99%
“…For example, if D(Y ) carries a (full, strong) exceptional collection one can construct a (full, strong) exceptional collection on D Sn (Y n ). The same holds for semi-orthogonal decompositions and tilting bundles; see [KS15,Sect. 4].…”
Section: Tautological Objects Under the Derived Mckay Correspondencementioning
confidence: 77%
“…where (−) ∨ ≔ RHom(−, O X ×X [2] ) is the derived dual. This notation for the functors mimicks that of [21].…”
Section: Fully Faithfulnessmentioning
confidence: 99%